The freedom of scientific research Bridging the gap between science and society - Giordano, Simona; Harris, John (Manchester University Press, 2020)
Never have the scope and limits of scientific freedom been more important or more under attack. New science, from artificial intelligence to genomic manipulation, creates unique opportunities to make the world a better place. But it also presents unprecedented dangers, which many believe threaten the survival of humanity and the planet. This collection, by an international and multidisciplinary group of leading thinkers, addresses three vital questions: (1) How are scientific developments impacting on human life and on the structure of societies? (2) How is science regulated, and how should it be regulated? (3) Are there ethical boundaries to scientific developments in some sensitive areas (e.g. robotic intelligence, biosecurity)? The contributors are drawn from many disciplines, and approach the issues in diverse ways to secure the widest representation of the many interests engaged. They include some of the most distinguished academics working in this field, as well as young scholars.